Analisis Pengaruh Penerapan Manajemen Sumber Daya Manusia Terhadap Produktivitas Kerja Kontraktor Pelaksana di Kabupaten Jembrana - I Ketut Suarjana; I Komang Agus Ariana (Institut Penelitian dan Pengembangan Mandalika (IP2MI), 2025)
Suboptimal human resource management remains a critical issue in construction project implementation, particularly in relation to labor productivity on-site. This study aims to analyze the influence of competence, work environment, and work motivation on the productivity of implementing contractors in Jembrana Regency. A quantitative approach was used, with data collected through a questionnaire distributed to 35 respondents working on several construction projects. The data were analyzed using validity testing, reliability testing, and descriptive analysis with SPSS software. The results indicate that all questionnaire items are valid and reliable. The average scores were 2.5877 for labor competence, 2.5886 for work environment, and 2.6143 for work motivation—all categorized as “High.” Productivity also fell within the “High” category with an average of 2.5657. These findings demonstrate that competence, work environment, and motivation positively influence contractor labor productivity. The study concludes that improving human resource management is a key strategy to support the achievement of productivity targets in construction projects.